Transnational capital and energy governance in the European Union. The case of natural gas - Moreno, Ana (Papeles de Europa, 2016)
The main objective of this paper is to analyze the liberalization of natural gas sector in Europe. Regarding the energy policy, we cannot consider the EU or its Member States just as agents of capital. However, granting them an autonomy according to which they develop their own interests, would lead us into a scenario that minimizes the role of capital. This research, then, follows the work of the Amsterdam School about transnational class formation. This approach underlines the need of the dominant class of exercising a collective agency to reproduce their dominance and to ensure that it articulates in concrete politics.
Keywords: Transnational capital; energy governance; European Union; natural gas; internal market